The effect of ecotype and season on the production and reproductive performance of Nguni cattle in Limpopo province of South Africa - Webb, E.C. (Edward Cottington) (University of Pretoria, 2022)
Dissertation (MSc Agric (Production Physiology and Product Quality))--University of Pretoria, 2021.